MOCO SIFAT SEBAGAI UPAYA MENUMBUHKEMBANGKAN BUDAYA LITERASI DI SDIT MUTIARA INSANI - AAN YUNIANTO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
At Mutiara Insani IT Elementary School, a few years earlier, there was a less literate atmosphere. Not many of them have the desire to read books. Be it in class or in the library. The students have not been able to feel that the activities of reading books, writing, composing, are very enjoyable. From this lack of interest in reading, the result is that student achievement is not very visible. Because as we know that books are windows of knowledge. The more he reads, the wider his knowledge will be, and his achievements will increase. Moreover, to produce a work of literacy, is something that is very far from wishful thinking. The problem-solving method used by the author to solve problems related to the lack of literacy culture at SDIT Mutiara Insani is